EFFECT OF THERAPY COMPLEMETER MEDITATION YOGA IN PATIENTS STRESS IN POLYCLINIC SOULS SPECIAL HOSPITAL REGIONAL PROVINCE OF SOUTH SULAWESI - Indirawaty, Indirawaty; Rahman, Rahman; Khaerunnisa, Khaerunnisa; Sumirah, Sumirah (Jurnal Kesehatan, 2018)
Yoga therapy in the world of nursing is known as the term complementary therapy. To avoid stress, one of the most efficient and has been done for centuries is to do yoga. The efficacy of yoga in helping to relieve stress is no doubt. Yoga helps keep people away from stress. According to Hawari (2008), the high incidence of stress in Indonesia is also the reason why stress should be prioritized handling because in 2008 recorded about 10% of the total population of Indonesia experiencing mental disorders or stress. The high level of stress is generally caused by economic pressures or poverty (Ministry of Health, 2009). General Purpose of this study To determine the influence of complementary therapies of yoga meditation on stress patients in Soul Polyclinic of Special Hospital Area of South Sulawesi Province. True Experiment Design True Experimental Design. Population in this study all stress patients who came to visit in Soul Polyclinic of Special Hospital Area of South Sulawesi Province amounted to 60 respondents consisting of 30 respondents in the group without intervention 30 people for the intervention group (Sugiono, 2011). The statistical test used: Mann Whey test and Wilcoxon test. The result of analysis test using Mann Whitney got data that value The result shows that Ha rejected and Ho accepted which mean there is no difference of the average of stress level in the group without intervention and intervention group during pre-test. The results of the test The results show that Ha accepted and Ho rejected which means there is a difference in the average level of stress in the group without intervention and intervention group at post-test. The above statistical test results give us an illustration that there are two groups in this study, that is the group of respondents treated only with pharmacology therapy, and one group of respondents treated with pharmacology therapy and complementary therapies of yoga meditation. The results showed that the group gave pharmacological therapy and complementary therapies had a higher cure rate than the group of respondents who received only pharmacological therapy